Serological investigation on swollen head syndrome in Indonesia - Aenuh R. Jusa; Retno D. Soejoedono; Cattleya S. Leksmono; Mastur A.R. Noor; Syamsul B. Siregar; Madsuki Pertadiredja (Hemera Zoa, 1992)
Clinical signs indicated that Swollen Head Syndrome (SHS) was suspected to be present in Indonesia. Serological investigation was carried out by collecting a number of 242 serum samples from Tangerang, Bogor, Cianjurm Ciawi, Cicurug dan Magelang, tested using serum neutralization (SN) test. The results of SN test indicated that SHS has been identified in these investigation areas. Based on the fact that these are the center for parent stock breeders it could be suspected taht the disease might have been speread to several areas of chicken farms in this country.It would be wise if a control program be formulated since this time, to ensure that everything is well prepared in case SHS situation develops into unfavorable condition.